2023
DOI: 10.3390/cancers15102816
|View full text |Cite
|
Sign up to set email alerts
|

Netrin Family Genes as Prognostic Markers and Therapeutic Targets for Clear Cell Renal Cell Carcinoma: Netrin-4 Acts through the Wnt/β-Catenin Signaling Pathway

Abstract: Clear cell renal cell carcinoma (ccRCC, or KIRC) is the most common type of kidney cancer, originating within the renal cortex. The current outcomes for early diagnosis and late treatment of ccRCC are unsatisfactory. Therefore, it is important to explore tumor biomarkers and therapeutic opportunities for ccRCC. In this study, we used bioinformatics methods to systematically evaluate the expression and prognostic value of Netrin family genes in ccRCC. Through our analysis, three potential biomarkers for ccRCC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…CYP27A1 mainly regulates cholesterol homeostasis using the CYP27A1/27-hydroxycholesterol (27-HC) axis as a mediator to regulate cell apoptosis and the cell cycle and is associated with good clinicopathological characteristics and prognosis [34]. Similarly, NTN4 is also associated with better survival rates facilitated by Wnt/β-Catenin signal transduction, and is positively correlated with the degree of in ltration of immune cells, including macrophages and neutrophils, as well as the immunosuppressive condition of tumors [35]. Previous studies have demonstrated that IGF2BP2 promotes the clearance, synthesis, metabolism, and growth of HNSCC cells and that its overexpression is a risk factor for poor prognosis in patients.…”
Section: Discussionmentioning
confidence: 99%
“…CYP27A1 mainly regulates cholesterol homeostasis using the CYP27A1/27-hydroxycholesterol (27-HC) axis as a mediator to regulate cell apoptosis and the cell cycle and is associated with good clinicopathological characteristics and prognosis [34]. Similarly, NTN4 is also associated with better survival rates facilitated by Wnt/β-Catenin signal transduction, and is positively correlated with the degree of in ltration of immune cells, including macrophages and neutrophils, as well as the immunosuppressive condition of tumors [35]. Previous studies have demonstrated that IGF2BP2 promotes the clearance, synthesis, metabolism, and growth of HNSCC cells and that its overexpression is a risk factor for poor prognosis in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Gene NTNG1 (Netrin G1), identified by GWAS(+HbA1c) and GWAS(+Urea), was a protein-coding gene. A study shows that the expression of NTNG1 was high in the retina and kidney in GTEx (https://www.gtexportal.org/home), and in the brain and kidney in HPA-RNA (Ke et al 2023). Abnormal methylation-modified differentially expressed genes of NTNG1 may be involved in inflammatory response and vascular remodeling in the process of Coronary artery ectasia (Yang et al 2023), which may likely influence the retinal vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…While a batch of evidence indicates the decreased expression of NTN4 in breast, pancreas, prostate, cervical, and colon cancer, elevated levels of this protein have also been documented in gastric cancer [12]. Moreover, the majority of the data on NTN4 expression in various cancers have been demonstrated in experimental models [14][15][16], and its role and clinical significance in human malignancies remain uncertain. In particular, the prognostic value of NTN4 as a biomarker in early detection and its association with HCC pathogenesis has not been explored.…”
Section: Introductionmentioning
confidence: 99%